The Relationship between Hardiness and Social Support with Psychological Well-Being in Final Year Students - Saharani, Diah Ayu; Karyani, Usmi (Universitas Muhammadiyah Surakarta, 2025)
Final year students often encounter academic and psychological challenges in completing their thesis as a graduation requirement. Pressures such as topic selection, repeated revisions, academic and family expectations, and limited guidance time can create stress and decrease adaptability, thereby disrupting psychological well-being. Psychological well-being, as conceptualized by Ryff and Keyes, represents a positive functioning state consisting of six dimensions: self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. Previous studies have shown that psychological well-being is influenced by both internal and external factors. Hardiness, a set of personality traits characterized by control, commitment, and challenge, acts as resilience against stress. Social support, defined as perceived help from family, friends, and significant others, is also considered an important element in maintaining well-being. However, the extent to which these two variables contribute to the psychological well-being of final year students in Indonesia remains underexplored.This study was conducted to examine the relationship between hardiness, social support, and psychological well-being among final year students at Universitas Muhammadiyah Surakarta. Using a quantitative correlational design, the study involved a sample of 357 students (130 males and 227 females, with an average age of 22 years) drawn from a population of approximately 10,005 students using simple random sampling. Data were collected through three validated instruments: the Psychological Well-Being Scale adapted from Ryff, the A Short Hardiness Scale based on Kobasa’s theory, and the Multidimensional Scale of Perceived Social Support (MSPSS). The instruments demonstrated acceptable levels of reliability, with Cronbach’s Alpha values of 0.863, 0.638, and 0.898 respectively. Data analysis was carried out using multiple linear regression through IBM SPSS version 25, supported by classical assumption tests.The results revealed that hardiness and social support simultaneously showed a significant relationship with psychological well-being, contributing 46.8% of the variance. Hardiness made the largest contribution at 45.76%, while social support contributed only 1.05%. Partial analysis indicated that hardiness was positively and significantly related to psychological well-being, whereas social support was not a significant predictor. Categorization further indicated that most students were in the medium category in terms of psychological well-being, hardiness, and social support, although a considerable proportion fell into the low and very low categories across these variables.These findings suggest that hardiness plays a more decisive role than social support in maintaining the psychological well-being of final year students. Students with high levels of hardiness tend to demonstrate resilience, adaptability, and emotional stability, which support them in coping with academic demands. Although social support did not show significant effects in this study, it remains a potential resource that, when combined with personal resilience, may enhance overall well-being. The findings are consistent with previous research highlighting the dominant role of hardiness in psychological functioning. Practical implications of this study include the importance of fostering resilience in students through structured time management, resilience training, and peer-support communities that help students navigate the challenges of thesis completion.The study concludes that both hardiness and social support are associated with psychological well-being, but hardiness is the dominant predictor. While the role of social support was not statistically significant, it cannot be disregarded, as it may become more effective when integrated with strong internal coping mechanisms. Future studies are advised to re-examine measurement tools, particularly the A Short Hardiness Scale, due to its marginal reliability, and to adopt instruments that classify social support functionally to better capture its multidimensional nature. In addition, incorporating qualitative approaches would enrich the understanding of the psychological experiences of final year students in a more contextual manner and broaden the distribution of respondents across faculties to improve generalizability.This study was ethically approved by the Health Research Ethics Committee of Dr. Moewardi General Hospital, Surakarta, Indonesia, with approval number 706/III/HREC/2025. All participants provided informed consent, and the confidentiality and anonymity of data were strictly maintained. The first author contributed to the conception, design, data collection, analysis, and writing of the manuscript, while the second author provided supervision, methodological guidance, critical review, and final approval. The authors declare no conflict of interest regarding this study.